Natural History of Atherosclerosis and Abdominal Aortic Intima-Media Thickness: Rationale, Evidence, and Best Practice for Detection of Atherosclerosis in the Young - Michael R. Skilton; David S. Celermajer; Erich Cosmi; Fatima Crispi; Samuel S. Gidding; Olli T. Raitakari; Elaine M. Urbina (MDPI, 2025)
Atherosclerosis underlies most myocardial infarctions and ischemic strokes. The timing of onset and the rate of progression of atherosclerosis differ between individuals and among arterial sites. Physical manifestations of atherosclerosis may begin in early life, particularly in the abdominal aorta. Measurement of the abdominal aortic intima-media thickness by external ultrasound is a non-invasive methodology for quantifying the extent and severity of early atherosclerosis in children, adolescents, and young adults. This review provides an evidence-based rationale for the assessment of abdominal aortic intima-media thickness-particularly as an age-appropriate methodology for studying the natural history of atherosclerosis in the young in comparison to other methodologies-establishes best practice methods for assessing abdominal aortic intima-media thickness, and identifies key gaps in the literature, including those that will identify the clinical relevance of this measure.